2014
DOI: 10.1088/0004-637x/788/1/26
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Dynamics Above Solar Flare Soft X-Ray Loop Tops

Abstract: We measure non-thermal motions in flare loop tops and above the loop tops using profiles of highly ionized spectral lines of Fe xxiv and Fe xxiii formed at multimillion-degree temperatures. Non-thermal motions that may be due to turbulence or multiple flow regions along the line of sight are extracted from the line profiles. The non-thermal motions are measured for four flares seen at or close to the solar limb. The profile data are obtained using the Extreme-ultraviolet Imaging Spectrometer on the Hinode spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 50 publications
8
45
1
Order By: Relevance
“…We can use Equations (12) and (13) to express the effective viscosity turb n in terms of two measurable quantities such as u turb and l turb . A crude estimate of the dimensionless constant in » -(for the value of l turb used in our simulations), which is well within the range reported by Doschek et al (2014) from Hinodeobservations. It is important to recall that other effects besides turbulence might contribute to reduce the instability growth rate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We can use Equations (12) and (13) to express the effective viscosity turb n in terms of two measurable quantities such as u turb and l turb . A crude estimate of the dimensionless constant in » -(for the value of l turb used in our simulations), which is well within the range reported by Doschek et al (2014) from Hinodeobservations. It is important to recall that other effects besides turbulence might contribute to reduce the instability growth rate.…”
Section: Discussionsupporting
confidence: 86%
“…One of them is the apparent development of the KH instability as some CMEs expand in the ambient corona, as shown by AIA/SDOimages (Foullon et al 2011;Ofman & Thompson 2011;Foullon et al 2013). The second one is that the coronal plasma seems to be in a turbulent state, as evidenced by the nonthermal broadening of coronal spectral lines measured from EIS/Hinodedata (Doschek et al 2008(Doschek et al , 2014Brooks & Warren 2011;Tian et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Doschek et al (2014), for example, only measured values of 20-60 km s −1 in Figures 5-7, the trend is not a function of temperature within an AR core. Rather, it is a trend between different AR cores.…”
Section: Summary and Discussionmentioning
confidence: 84%
“…For example, high-resolution soft X-ray images from the TRACE and Hinode satellites have confirmed that reconnection of magnetic fields in the upper atmosphere of the Sun plays a key role in producing the explosive ejection of solar material outward into the solar system (Goff et al 2005;Doschek et al 2014). Such eruptive events, known as coronal mass ejections or CMEs, are responsible for major magnetic storms on Earth (Webb et al 2000).…”
Section: Introductionmentioning
confidence: 99%